The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/myc.13104
|View full text |Cite
|
Sign up to set email alerts
|

Low level of antifungal resistance of Candida glabrata blood isolates in Turkey: Fluconazole minimum inhibitory concentration and FKS mutations can predict therapeutic failure

Abstract: Background Candida glabrata is the third leading cause of candidaemia in Turkey; however, the data regarding antifungal resistance mechanisms and genotypic diversity in association with their clinical implication are limited. Objectives To assess genotypic diversity, antifungal susceptibility and mechanisms of drug resistance of C glabrata blood isolates and their association with patients' outcome in a retrospective multicentre study. Patients/Methods Isolates from 107 patients were identified by ITS sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…We also revealed correlation between the genotype cluster and patient mortality, which has been previously shown for C. glabrata ( Byun et al, 2018 ; Arastehfar et al, 2019a ). The mortality rate observed in this study is similar to those reported for C. tropicalis in Iran ( Arastehfar et al, 2020a ), Italy ( Montagna et al, 2013 ), and the United States ( Andes et al, 2016 ), and to that observed for C. glabrata in Turkey ( Arastehfar et al, 2020e ). Collectively, these findings emphasize the importance of using genotyping techniques in clinical settings, which may provide insightful observations with predictive prognostic values.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We also revealed correlation between the genotype cluster and patient mortality, which has been previously shown for C. glabrata ( Byun et al, 2018 ; Arastehfar et al, 2019a ). The mortality rate observed in this study is similar to those reported for C. tropicalis in Iran ( Arastehfar et al, 2020a ), Italy ( Montagna et al, 2013 ), and the United States ( Andes et al, 2016 ), and to that observed for C. glabrata in Turkey ( Arastehfar et al, 2020e ). Collectively, these findings emphasize the importance of using genotyping techniques in clinical settings, which may provide insightful observations with predictive prognostic values.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to a previous study reporting the absence of azole-resistant C. tropicalis ( Arikan-Akdagli et al, 2019 ), however, we identified 18.6% ANS C. tropicalis isolates, among which 93 and 58% were cross-resistant to three azoles or fluconazole + voriconazole, respectively. Importantly, we observed an alarming rate (40–50%) of ANS isolates in some hospitals in 2019, which is also documented in other studies ( Arendrup et al, 2011 ; Chen et al, 2019 ; Pfaller et al, 2019 ); these statistics require particular attention, especially in the countries where azoles are the main antifungals used for candidemia therapy ( Sellami et al, 2011 ; Singh et al, 2018 ; Arastehfar et al, 2019a , 2020e ). Notable variations in the rate of azole-resistant isolates (0–100%) observed among the analyzed hospitals could be attributed to differences in intervention strategies, including the use of azoles and infection control practices.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Therefore, isolates displaying echinocandin resistance without known mutations in the HS regions may harbor non-synonymous mutations located anywhere in the FKS genes. Importantly, it has been documented that occasionally C. glabrata blood isolates carrying mutation in HS1-Fks1 (S629T) are fully susceptible to echinocandins, while the patient infected with such isolate showed therapeutic failure [107]. Therefore, combination of both antifungal susceptibility testing (AFST) and FKS sequencing can more precisely predict therapeutic failure when treating candidemia patients with echinocandins.…”
Section: Candida Glabratamentioning
confidence: 99%